The Development of A Physics Teaching Module Using Multimodel to Improve Students' Understanding of Concepts - Nor Anisa; Sarah Miriam; Abdul Salam (Berkala Ilmiah Pendidikan Fisika, 2025)
Conceptual understanding is a fundamental component that students must possess in science learning. However, various studies have shown that students' conceptual understanding is still not taught optimally. The availability of teaching modules, supported by appropriate instructional models, can contribute significantly to improving students’ conceptual understanding. This study aims to develop a physics teaching module on the topic of momentum and impulse using a multimodel approach that is valid, practical, and effective in enhancing students’ conceptual understanding. This research employed a Research and Development (R&D) design using the ADDIE model. The research subjects consisted of 21 students from Class XI at an SMA in Amuntai City. The instruments used included a module validation sheet, an observation sheet for learning implementation, and a learning outcome test. The results showed that the developed teaching module demonstrated a very high level of validity with an average score of 3.37. The module, which includes learning materials, student worksheets, and a learning outcome test, was also categorized as highly valid. Observations of the module implementation over three meetings indicated a very good level of practicality. Moreover, the module was considered effective based on an n-gain score of 0.60. Therefore, the multimodel-based physics teaching module developed in this study is feasible for use in improving students' conceptual understanding in physics learning. This finding implies that the development of teaching modules using multimodal approaches can be a potential alternative strategy for educators to enhance students' understanding of concepts and make learning more meaningful.